The Impact of Utilizing Songs on Enhancing English Vocabulary Development in Elementary Students at Private Schools - Daw, Aida Mohammed Ali; Neji, Asma Abd-Alsalam; Kesel, Fatima Ahmed; Al-Garary, Yasmen Esmaeil; Salem, Mona M. M. (The annual Scientific Conference for Under and Postgraduate Students at the University., 2023)
This paper aims to examine the impact of the use of songs on the development of English vocabulary in the elementary grades and also identify the use of songs by teachers in their classrooms. The paper shows some previous studies that support the research. It also focuses on the way in which data was collected in this study is a questionnaire that was directed to a sample of 16 teachers who were selected from five private schools in Libya (Zliten) with the aim of providing a deeper analysis of the effect of utilizing songs on vocabulary progress. The results of the questionnaire showed that many teachers have encouraging outlooks about the use of songs, including developing vocabulary and consolidating it in the minds of students and the correct pronunciation of words, as well as developing listening and speaking skills. Some teachers use songs to change the routine and create an atmosphere of activity within it. Based on the results of the analysis, some recommendations for teachers in schools come from research students at Alasmarya Islamic University about the intensification of the use of song activities and strategies for the elementary grades.
Keywords: Effectiveness; English vocabulary; Elementary Schools; Using songs; Zliten